2020
DOI: 10.3390/foods9040439
|View full text |Cite
|
Sign up to set email alerts
|

Livestock-Associated Methicillin-Resistant Staphylococcus aureus (MRSA) in Purulent Subcutaneous Lesions of Farm Rabbits

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) are one of the main pathogens associated with purulent infections. MRSA clonal complex 97 (CC97) has been identified in a wide diversity of livestock animals. Therefore, we aimed to investigate the antibiotic resistance profiles of MRSA strains isolated from purulent lesions of food-producing rabbits. Samples from purulent lesions of 66 rabbits were collected in a slaughterhouse in Portugal. Samples were seeded onto ORSAB plates with 2 mg/L of oxacillin for MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 64 publications
(68 reference statements)
1
17
0
2
Order By: Relevance
“…This result is consistent with our previous study, in which all of the 281 S. aureus isolates recovered from rabbits in Fujian Province were MSSA (Wang et al, 2019a). However, the colonisation of MRSA in rabbits was detected in Italy and the Iberian Peninsula (Agnoletti et al, 2014;Moreno-Grúa et al, 2018;Silva et al, 2020), and transmission of MRSA from rabbit to human has been previously reported (Agnoletti et al, 2014). Therefore, we should be on the alert for the potential emergence of MRSA in rabbits in Fujian Province.…”
Section: Discussionsupporting
confidence: 91%
“…This result is consistent with our previous study, in which all of the 281 S. aureus isolates recovered from rabbits in Fujian Province were MSSA (Wang et al, 2019a). However, the colonisation of MRSA in rabbits was detected in Italy and the Iberian Peninsula (Agnoletti et al, 2014;Moreno-Grúa et al, 2018;Silva et al, 2020), and transmission of MRSA from rabbit to human has been previously reported (Agnoletti et al, 2014). Therefore, we should be on the alert for the potential emergence of MRSA in rabbits in Fujian Province.…”
Section: Discussionsupporting
confidence: 91%
“…Shortly afterwards, the New Yorker/Japanese clone ST5-t067 and, more recently, the ST105-t002 clone appeared as the second most prevalent clones [ 35 ] (which was found in five strains from our study). For the other clones in this study, the ST- spa association had already been described for several cases: the clone ST8-t008 in humans and pigs in Norway; the ST22-t020 and the ST5-t179 in the community in Portugal; the ST239-t932 in Malaysia; the ST5-t062 in Brazil; the CC45-t132 and CC25-t078 in Lebanon; the ST239-t030 in China; the ST8-t104 in Angola; the ST15-t084 in Iran associated with hospitals; the ST22-t022 in USA, Canada, Europe, Middle East, Asia, and Australia/New Zealand; the CC5-t688 in USA associated with the community; ST22-t747/t910/t2357 and CC5-t10682 in Portugal associated with hospitals and the community; the CC5-t1094 in rabbits in Portugal; and the ST72-t148 in humans, gorillas, and chimpanzees in Gabon [ 2 , 4 , 22 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Community-based strains used to be associated with ST1, ST8, ST30, ST72, and ST80; however, except for ST1 and ST80, the other ST were found in this study in hospital-acquired strains.…”
Section: Discussionmentioning
confidence: 99%
“…A distinct distribution was observed in strains collected from animals, since here the predominant group was III, unlike other studies such as Smyth et al [ 64 ], and there were representatives of all four groups in this samples. Other studies have demonstrated the predominance of group III, but in strains of MRSA from deer [ 65 ], sheep [ 66 ], and rabbit [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with a wide variety of diseases, such as skin lesions, wound infections, mastitis, toxic shock syndromes, arthritis, endocarditis, osteomyelitis, and episodes of food poisoning [ 5 , 6 , 7 ]. In rabbits, this bacterium is an inhabitant of the skin, but it is also one on the main pathogens related to suppurative lesions [ 8 ]. For this reason, S. aureus could be used as indicator for the level of antimicrobial use in farms.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the presence of MRSAs in Italian rabbit breeding and the relationship between antibiotic use in farms and resistance have been evaluated [ 9 , 10 ]. High virulent strains (HV) were detected in Belgium, France, Greece, Italy, Portugal, Spain, and Hungary [ 8 , 11 , 12 ]. On the other hand, a recent study by Nemet et al [ 12 ] provided evidence that low virulent (LV) strains can act as pathogens in rabbits.…”
Section: Introductionmentioning
confidence: 99%